Две версии одного события (Исторический комментарий к анекдоту С. Д. Довлатова) [Two Versions of the Same Event: A Historical Note to Sergei Dovaltov’s Anecdote] - Fyaduta, Alexander (Slavica Revalensia, 2017)
The article analyzes an anecdote about a Soviet official visiting Poland after WWII as represented in Sergei Dovlatov’s cycle “Solo na undervude” (1980), and provides the anecdote’s alternative version. This alternative version contains exactly the same plot, yet varies on the plane of characters’ names, and in one detail in the ending. Despite these slight variations, both the Dovlatov version and the version the article’s author learned from the Polish intellectual and former political prisoner Adam Michnik, are centered on exactly the same theme: the theme of the opposition of a writer to the power of a totalitarian state.